Trick or treat? The Brexit effect on immigrants' wellbeing in the UK - Cinzia Rienzo (Global Labor Organization (GLO), 2020)
This paper is the first attempt to analyse the effect of the Brexit Referendum results on subjective well-being of immigrants living in the UK. Using the national representative UK Household Longitudinal Study (Understanding Society) data and adopting a difference-in-differences estimates, we define natives as control group, and different sub-groups of immigrants as treatment groups. The current analysis suggests that following the EU Referendum Results Non-EU migrants experienced an improvement in both mental health and life satisfaction relative to the UK natives. The results are robust to several robustness checks. Among others, we account for unobserved individual fixed effects and for unbalanced panel data. The results are consistent with the idea that the end of free movement for EU immigrants has alleviated the sense of discrimination and frustration felt by Non-EU immigrants results mainly of the toughened visa restrictions enforced since 2010 by the UK Government.
Keywords: O15; J61; 330; immigration; Subjective Wellbeing; Brexit